(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
The Uses and Gratification Theory over the years has been found to be the central theory of Communication which aptly describes what exactly people want to do when given the option to use the media. It has been seen that the development of the social media has bestowed a brand-new lease of life expectancy to this old-fashioned and obsolete theory. The reason why this study is being attempted is to explore the existing functions of the Theory of Uses and Gratification among university students who use tobacco. This research has employed Surveys and focus group discussions to elicit information from 1,000 respondents from the two major provinces of Pakistan: Sindh and Punjab, over two (02) year period beginning in 2016. The present quantitative study, while adopting survey as method of research is an effort to examine the views of 1,000 randomly chosen respondents under the age of 25, preferably from educational institutions, including Sindh and Punjab medical colleges. The study confirms the radical upsurge in the present usage of the social media by the masses which has once again renewed a belief in the once considered antiquated Uses and Gratification Theory functions and have in the process provided a plethora of the media uses that in its original form that the traditional media never could.